2006
DOI: 10.1007/s11262-006-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

New HPV-16 European and non-European variants in Central Brazil

Abstract: HPV-16 is the most prevalent human papillomavirus genotype found in cervical intraepithelial neoplasias. The regulatory region of the HPV genome, LCR, has several binding sites for cellular and viral transcription factors, and nucleotide substitutions in this genomic region can interfere with the viral oncogenic expression. The present study aims to determine the LCR variability of European and non-European HPV-16 variants found in Brazil. Through automated sequencing, it was possible to characterize the LCR o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…This was also found in southeastern (Villa et al, 2000) and central Brazil (Cruz et al, 2004;Alencar et al, 2007). Variants of HPV type 16 are typically classified into European, African, Asian-American, and North-American, or Amerindian (Yamada et al, 1997).…”
Section: Prevalence Of the Types Of Hpvmentioning
confidence: 85%
See 1 more Smart Citation
“…This was also found in southeastern (Villa et al, 2000) and central Brazil (Cruz et al, 2004;Alencar et al, 2007). Variants of HPV type 16 are typically classified into European, African, Asian-American, and North-American, or Amerindian (Yamada et al, 1997).…”
Section: Prevalence Of the Types Of Hpvmentioning
confidence: 85%
“…Cervical cancer is the most common disease in Brazilian women, and infection by HPV is the main risk factor for development of this pathology. In Brazil, most studies of HPV were conducted in southeastern (Villa et al, 2000) or in central regions of the country (Cruz et al, 2004;Alencar et al, 2007;Cerqueira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…HPV16 variants coevolved with the three major phylogenetic ethnic groups-Africans, Caucasians, and Asians. These variants clustered into five distinct groups: European (E), Asian (As), Asian-American (AA) which originated from Central and South America, African 1 (Af-1), and African 2 (Af-2) [14,15] and some authors have suggested that certain HPV-16 non-European variants are associated with a higher risk of cervical intraepithelial neoplasia and invasive cancer [16]. In a critical genome region of the HPV 16 variant such as the long control region (LCR), the E6 and the E2 genes may be associated with the oncogenic potential of HPV [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In a critical genome region of the HPV 16 variant such as the long control region (LCR), the E6 and the E2 genes may be associated with the oncogenic potential of HPV [17,18]. Molecular characterization of the variability found in the LCR may contribute to better understand the association of HPV16, especially the nonEuropean variants, with a potentially greater oncogenicity [16]. Some previous reports have studied HPV16 at different stages of cervical cancer by examining the distribution of the LCR, E7, E6, L1, L2, and E2 polymorphisms [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous variants of the prototypical HPV-16 URR sequence (17) have been described (1,10,36,66,67); similar sequence variation has been observed in other HR and low-risk HPV types (2,8,9,26,42,45). Some of the nucleotide changes exhibit characteristic geographic distributions and have been grouped into evolutionary variants: the European (E), North American 1 (NA1), and Asian-American (AA) variants.…”
mentioning
confidence: 76%